The Hidden Costs of Workaholism: Economic and Psychological Consequences in Micro Family Businesses (European Journal of Marketing and Economics, 2026)
This study examines the dual economic and psychological effects of workaholism in micro-sized, family-owned enterprises (1–9 employees). Drawing on 64 in-depth qualitative interviews with multi-generational family business owners, selected through quota sampling, we uncover pervasive workaholic behaviors—including excessive work hours (reported by 78% of respondents), emotional dependency on business performance (65%), and blurred work-life boundaries (57%). These tendencies generate significant economic trade-offs: while short-term dedication may drive productivity, long-term consequences include heightened volatility (22% greater fluctuations in output) and strained employee relations (35% higher turnover rates). Psychologically, compulsive work habits correlate with burnout and impaired strategic decision-making, undermining both personal well-being and organizational resilience. Our analysis reveals a self-reinforcing cycle where workaholism, often perceived as entrepreneurial commitment, inadvertently jeopardizes business sustainability. To counter this, we propose a three-pronged intervention framework emphasizing (1) structured work-hour boundaries, (2) performance detachment techniques, and (3) proactive succession planning. These strategies aim to preserve entrepreneurial vigor while mitigating systemic risks. The study advances the discourse on mental health in small business economics, offering empirically grounded recommendations for family enterprises and policymakers seeking to balance productivity with sustainable management practices.
Keywords: workaholism, micro-family businesses, entrepreneurial well-being, small business sustainability, work-life balance, compulsive entrepreneurship, psychological economics